Self-lubricating nickel-based composite material and powder metallurgy forming method and application thereof

The self-lubricated nickel-based composite material was prepared by powder metallurgy molding, which solved the problem of limited thickness of the nickel-based self-fused alloy coating, and achieved the preparation of wear-resistant and corrosion-resistant gaskets with a thickness of more than 1 mm, which improved the wear resistance and self-lubricating properties of the material.

CN119753426APending Publication Date: 2025-04-04ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411776353.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The coating thickness of existing nickel-based self-fusion alloys formed by thermal spraying is limited, making it difficult to meet the effect requirements in some applications.

Method used

The self-lubricated nickel-based composite material was prepared by powder metallurgy molding. By adding nickel-clad graphite and TiC, combined with powdered paraffin as a binder, the process steps of mixing, pressing and vacuum sintering were prepared to produce wear-resistant and corrosion-resistant gaskets with a thickness of more than 1 mm.

Benefits of technology

The defect of limited thickness of the thermal spray coating method was overcome, and a wear-resistant and corrosion-resistant gasket with a larger thickness was prepared, which significantly improved the applicability and durability in high wear environments, and improved the wear resistance and self-lubricating properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753426A_ABST
    Figure CN119753426A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material science, and discloses a self-lubricating nickel-based composite material and a powder metallurgy forming method and application thereof, the self-lubricating nickel-based composite material comprises the following raw materials by mass percentage: 4.9%-6.8% of nickel-coated graphite powder, 9.7%-11.7% of TiC powder, 81.6%-82.5% of Ni60A powder and 2.4%-2.9% of a binder; the method comprises the following steps: weighing nickel-coated graphite powder, TiC powder, Ni60A powder and a binder in corresponding mass percent; the alloy powder doped with the binder is mixed, and the mixed powder is weighed and added into a wafer mold to be pressed; and putting the pressed sample into a vacuum sintering furnace, carrying out dewaxing sintering treatment by using the vacuum sintering furnace, and carrying out metallurgical sintering treatment after dewaxing sintering is completed, so as to obtain the circular wear-resistant and corrosion-resistant gasket. The wear resistance of the material is enhanced, the friction coefficient is reduced, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material science, and in particular to a self-lubricating nickel-based composite material and a powder metallurgy forming method and application thereof. Background Art

[0002] Nickel-based self-fluxing alloy is a special type of metal alloy, mainly composed of nickel (Ni) as the matrix element, and contains other metals such as chromium (Cr), silicon (Si), carbon (C) and other components, with self-fluxing and excellent wear and corrosion resistance. An important feature of self-fluxing alloy is that it can spontaneously melt and form a dense coating during heating without the need for external flux or additional welding materials.

[0003] Nickel-based self-fluxing alloys are mainly used to repair metal surfaces and enhance wear and corrosion resistance, usually through thermal spraying of alloy powders. However, the coating thickness that can be formed by thermal spraying is limited, usually not exceeding 1 mm, which limits its effect in certain applications. Using powder metallurgy as a molding method, samples of various shapes can be prepared. By adding components such as lubricating phases and hard phases, the wear and corrosion resistance of the samples can be further improved. Therefore, the present invention proposes a self-lubricating nickel-based composite material and its powder metallurgy molding method and application. Summary of the invention

[0004] The embodiment of the present invention provides a self-lubricating nickel-based composite material and a powder metallurgy forming method and application thereof to solve the above-mentioned technical problems in the prior art.

[0005] In order to have a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended to be a general review, nor is it intended to identify key / important components or to delineate the scope of protection of these embodiments. Its only purpose is to present some concepts in a simple form as a preface to the detailed description that follows.

[0006] According to a first aspect of an embodiment of the present invention, a self-lubricating nickel-based composite material is provided.

[0007] In one embodiment, the self-lubricating nickel-based composite material comprises the following raw materials in percentage by mass:

[0008] Nickel-coated graphite powder 4.9%-6.8%, TiC powder 9.7%-11.7%, Ni60A powder 81.6%-82.5% and binder 2.4%-2.9%.

[0009] In one embodiment, the particle size of the nickel-coated graphite powder is 80 μm-100 μm, the particle size of the TiC powder is 1 μm-15 μm, and the particle size of the Ni60A powder is 60 μm-80 μm.

[0010] In one embodiment, the binder is powdered paraffin.

[0011] According to a second aspect of an embodiment of the present invention, a powder metallurgy forming method of a self-lubricating nickel-based composite material is provided.

[0012] In one embodiment, the powder metallurgy forming method of the self-lubricating nickel-based composite material comprises:

[0013] The mass percentage of each raw material is set based on the metallurgical forming requirements, and the corresponding mass percentages of nickel-coated graphite powder, TiC powder, Ni60A powder and binder are weighed;

[0014] The alloy powder mixed with the binder is mixed by using a mixing device, and the mixed powder is weighed and added into a disc mold for pressing to obtain a sample;

[0015] The pressed sample is placed in a vacuum sintering furnace, dewaxing and sintering treatment is performed in the vacuum sintering furnace, and metallurgical sintering treatment is performed after the dewaxing and sintering is completed to obtain a circular wear-resistant and corrosion-resistant gasket.

[0016] In one embodiment, the mass percentages of the raw materials include: 4.9%-6.8% nickel-coated graphite powder, 9.7%-11.7% TiC powder, 81.6%-82.5% Ni60A powder and 2.4%-2.9% binder.

[0017] In one embodiment, the mass percentages of the raw materials include: 4.9% nickel-coated graphite powder, 9.7% TiC powder, 82.5% Ni60A powder and 2.9% binder.

[0018] In one embodiment, the particle size of the nickel-coated graphite powder is 80 μm-100 μm, the particle size of the TiC powder is 1 μm-15 μm, and the particle size of the Ni60A powder is 60 μm-80 μm.

[0019] In one embodiment, the binder is powdered paraffin.

[0020] In one embodiment, the mixing device is a powder mixer, and the rotation speed of the mixing process is 1000 rpm, and the mixing time is 2 minutes.

[0021] In one embodiment, the mass of the mixed powder is 6 g, the diameter of the disc mold is 200 mm, and the pressure during the pressing process is 24 t.

[0022] In one embodiment, the vacuum degree in the chamber of the vacuum sintering furnace during the dewaxing sintering process is -1 bar.

[0023] In one embodiment, the dewaxing sintering process includes two stages, wherein the sintering temperature of the first stage is 300°C-320°C, and the sintering time is 30min-60min, the sintering temperature of the second stage is 380°C-400°C, and the sintering time is 30min-60min, and the heating rate from room temperature to the first and second sintering stages is 3°C / min.

[0024] In one embodiment, the dewaxing sintering process includes two stages, wherein the sintering temperature of the first stage is 300° C. and the sintering time is 1 hour, and the sintering temperature of the second stage is 400° C. and the sintering time is 1 hour.

[0025] In one embodiment, the furnace does not need to be opened during the metallurgical sintering treatment, and the temperature is continued to rise to 1040°C-1050°C at a heating rate of 10°C / min. After the sintering time is 100min-120min, the furnace is cooled to 150°C and taken out.

[0026] In one embodiment, the furnace does not need to be opened during the metallurgical sintering process, and the temperature is continuously raised to 1050°C at a rate of 10°C / min. After being kept at 1050°C for 2 hours, the furnace is cooled to 150°C and taken out.

[0027] According to a third aspect of an embodiment of the present invention, there is provided use of the self-lubricating nickel-based composite material or the self-lubricating nickel-based composite material prepared by the powder metallurgy forming method of the self-lubricating nickel-based composite material in wear-resistant parts.

[0028] The technical solution provided by the embodiment of the present invention may have the following beneficial effects:

[0029] The present invention can prepare wear-resistant and corrosion-resistant gaskets with a thickness of more than 1 mm through a powder metallurgy method, which overcomes the defect of limited coating thickness in thermal spraying technology, thereby improving the applicability and durability in high-wear environments. At the same time, after adding nickel-coated graphite and titanium carbide, the wear resistance and self-lubricating properties of the sample are significantly improved. This combination not only enhances the wear resistance of the material, but also reduces the friction coefficient and prolongs the service life. In addition, powder metallurgy technology allows the manufacture of samples of various shapes, providing greater design freedom to meet specific application requirements. In summary, the products of the present invention can be widely used in harsh scenarios of corrosion and wear, such as wear-resistant and corrosion-resistant gaskets, to meet the industry's demand for high-performance materials.

[0030] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0032] Figure 1 is a flow chart of a powder metallurgy forming method of a self-lubricating nickel-based composite material according to an exemplary embodiment;

[0033] Figure 2 is a schematic diagram of the wear scar depth and wear scar profile of Example 1;

[0034] Figure 3 is a schematic diagram of the wear scar depth and wear scar profile of Example 2;

[0035] Figure 4 is a schematic diagram of the wear scar depth and wear scar profile of Example 3;

[0036] Figure 5 is a schematic diagram of the wear scar depth and wear scar profile of Example 4;

[0037] Figure 6 is a schematic diagram of the wear scar depth and wear scar profile of Comparative Example 1;

[0038] Figure 7 It is a schematic diagram of the change of the friction coefficient of the samples obtained in Examples 1, 2, 3, 4 and Comparative Example 1 over time in the friction and wear test;

[0039] Figure 8 It is a schematic diagram of the changes in density and porosity of four samples with different compositions, T5G5, T5G10, T10G5, T10G10 and T0G0, under different sintering parameters;

[0040] Fig. 9 It is a schematic diagram of the depth and cross-sectional area of ​​the wear scars of T5G5, T5G10, T10G5, T10G10 and T0G0 in the friction and wear experiment. DETAILED DESCRIPTION

[0041] The following description and accompanying drawings fully illustrate the specific embodiments of this article so that those skilled in the art can practice them. Parts and features of some embodiments may be included in or replace parts and features of other embodiments. The scope of the embodiments of this article includes the entire scope of the claims, as well as all available equivalents of the claims. Herein, the terms "first", "second", etc. are only used to distinguish one element from another, without requiring or implying any actual relationship or order between these elements. In fact, the first element can also be called the second element, and vice versa. Moreover, the terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the structure, device or equipment including a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also include elements inherent to such structure, device or equipment. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the structure, device or equipment including the elements. Each embodiment is described in a progressive manner herein, and each embodiment focuses on the differences from other embodiments, and the same and similar parts between the embodiments can be referred to each other.

[0042] As used herein, the term "plurality" means two or more than two, unless otherwise specified.

[0043] In this document, the character " / " indicates that the preceding and following objects are in an "or" relationship. For example, A / B means: A or B.

[0044] In this article, the term "and / or" is a description of the association relationship between objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or, A and B.

[0045] It should be understood that, although the various steps in the flow chart are displayed in sequence according to the indication of the arrows, these steps are not necessarily executed in sequence according to the order indicated by the arrows. Unless there is a clear description in this article, the execution of these steps is not strictly limited in order, and these steps can be executed in other orders. Moreover, at least a portion of the steps in the figure may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and the execution order of these sub-steps or stages is not necessarily to be carried out in sequence, but can be executed in turn or alternately with other steps or at least a portion of the sub-steps or stages of other steps.

[0046] In the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0047] According to one aspect of the present invention, a self-lubricating nickel-based composite material is provided, comprising the following raw materials in percentage by mass:

[0048] Nickel-coated graphite powder 4.9%-6.8%, TiC powder 9.7%-11.7%, Ni60A powder 81.6%-82.5% and binder 2.4%-2.9%.

[0049] In this optional embodiment, the particle size of the nickel-coated graphite powder is 80 μm-100 μm, the particle size of the TiC powder is 1 μm-15 μm, and the particle size of the Ni60A powder is 60 μm-80 μm.

[0050] In this optional embodiment, the binder is powdered paraffin.

[0051] According to another aspect of the present invention, Figure 1 An embodiment of a powder metallurgy forming method of a self-lubricating nickel-based composite material of the present invention is shown.

[0052] In this optional embodiment, the powder metallurgy forming method of the self-lubricating nickel-based composite material comprises:

[0053] Step S101, setting the mass percentage of each raw material based on metallurgical forming requirements, and weighing the corresponding mass percentages of nickel-coated graphite powder, TiC powder, Ni60A powder and binder;

[0054] Step S103, using a mixing device to mix the alloy powder mixed with the binder, and weighing the mixed powder and adding it into a round wafer mold for pressing to obtain a sample;

[0055] Step S105, placing the pressed sample into a vacuum sintering furnace, performing dewaxing and sintering treatment in the vacuum sintering furnace, and performing metallurgical sintering treatment after the dewaxing and sintering are completed to obtain a circular wear-resistant and corrosion-resistant gasket.

[0056] In this optional embodiment, the mass percentages of the raw materials include: nickel-coated graphite powder 4.9%-6.8%, TiC powder 9.7%-11.7%, Ni60A powder 81.6%-82.5% and binder 2.4%-2.9%.

[0057] In this optional embodiment, the mass percentages of the raw materials include: 4.9% nickel-coated graphite powder, 9.7% TiC powder, 82.5% Ni60A powder and 2.9% binder.

[0058] In this optional embodiment, the particle size of the nickel-coated graphite powder is 80 μm-100 μm, the particle size of the TiC powder is 1 μm-15 μm, and the particle size of the Ni60A powder is 60 μm-80 μm.

[0059] In this optional embodiment, the binder is powdered paraffin.

[0060] In this optional embodiment, the mixing device is a powder mixer, and the rotation speed of the mixing process is 1000 rpm, and the powder mixing time is 2 minutes.

[0061] In this optional embodiment, the mass of the mixed powder is 6 g, the diameter of the disc mold is 200 mm, and the pressure during the pressing process is 24 t.

[0062] In this optional embodiment, the vacuum degree in the chamber of the vacuum sintering furnace during the dewaxing sintering process is -1 bar.

[0063] In this optional embodiment, the dewaxing sintering process includes two stages, wherein the sintering temperature of the first stage is 300°C-320°C, and the sintering time is 30min-60min, and the sintering temperature of the second stage is 380°C-400°C, and the sintering time is 30min-60min, and the heating rate from room temperature to the first and second sintering stages is 3°C / min.

[0064] In this optional embodiment, the dewaxing sintering process includes two stages, wherein the sintering temperature of the first stage is 300° C. and the sintering time is 1 hour, and the sintering temperature of the second stage is 400° C. and the sintering time is 1 hour.

[0065] In this optional embodiment, there is no need to open the furnace during metallurgical sintering treatment, and the temperature continues to rise to 1040°C-1050°C at a heating rate of 10°C / min. After sintering for 100min-120min, the furnace is cooled to 150°C and taken out.

[0066] In this optional embodiment, there is no need to open the furnace during the metallurgical sintering treatment, and the temperature continues to rise to 1050°C at a rate of 10°C / min. After being kept at 1050°C for 2 hours, it is cooled to 150°C with the furnace and taken out.

[0067] According to another aspect of the present invention, there is provided use of the self-lubricating nickel-based composite material or the self-lubricating nickel-based composite material prepared by the powder metallurgy forming method of the self-lubricating nickel-based composite material in wear-resistant parts.

[0068] In order to facilitate the understanding of the above technical solution of the present invention, the above technical solution is further described below from specific embodiments and comparative examples, as follows:

[0069] Embodiment 1:

[0070] Ni60A powder with a particle size of 60-80 μm, TiC powder with a particle size of 1-15 μm and nickel-coated graphite powder with a particle size of 80-100 μm are selected and used; alloy powders are prepared, wherein, by mass fraction, Ni60A self-fluxing alloy powder accounts for 85%, nickel-coated graphite accounts for 5%, and titanium carbide accounts for 10%; a binder is added, wherein the binder is powdered paraffin wax, and the addition amount is 3% of the alloy powder; the alloy powder mixed with the paraffin wax powder is mixed by a powder mixer, the mixing speed is 1000 rpm, and the mixing time is 2 minutes; 6 g of powder is weighed and added into a disc mold with a diameter of 20 mm for pressing, and the pressure is 24 tons.

[0071] Put the pressed sample into the vacuum sintering furnace, and after the vacuum degree in the furnace chamber is pumped to -1 bar, dewaxing sintering is carried out to decompose the paraffin in the powder into gas and remove it. Dewaxing sintering is divided into two stages. The sintering temperature of the first stage is 300℃, the sintering time is 1 hour, and the sintering temperature of the second stage is 400℃, the sintering time is 1 hour. The heating rate from room temperature to the first and second sintering stages is controlled at 3℃ / min. After dewaxing sintering is completed, metallurgical sintering is carried out. There is no need to open the furnace, continue to heat up to 1050℃, the heating rate is 10℃ / min, keep warm at 1050℃ for 2 hours, cool to 150℃ with the furnace and take it out.

[0072] like Figure 2 As shown in the figure (a is the surface morphology of the wear scar, and b is the cross-sectional profile of the wear scar), it is a schematic diagram of the wear scar depth and wear scar profile of the sample (T10G5) in Example 1, with a TiC addition of 10% and a nickel-coated graphite addition of 5%, a sintering parameter of 1050°C, and a reciprocating friction condition of 40N, 5mm reciprocating stroke, and 300t / min reciprocating speed.

[0073] Figure 2 The surface morphology and cross-sectional profile of the wear scar of T10G5 are given. Figure 2 (a) It can be observed that the wear scar surface is relatively uniform, with small and uniformly distributed pits. The increase in TiC content greatly enhances the hardness and wear resistance of the surface, and the graphite remains in the small pits, providing a more effective friction reduction effect. From the cross-sectional profile of the wear scar, the wear scar depth of the T10G5 sample is relatively shallow, at about 6μm, which is the result of the reinforcing effect of TiC and the lubricating effect of nickel-coated graphite. In particular, with the support of sufficient TiC, the friction reduction effect of nickel-coated graphite is better exerted, so that the material surface exhibits better wear resistance during the wear process.

[0074] With the support of the hard phase TiC, the hardness of the material surface is greatly improved, resulting in less severe plastic deformation during wear. At the same time, nickel-coated graphite reduces the severity of this adhesion effect through friction reduction, making the wear marks more uniform and significantly reducing the wear depth.

[0075] Embodiment 2:

[0076] Ni60A powder with a particle size of 60-80 μm, TiC powder with a particle size of 1-15 μm and nickel-coated graphite powder with a particle size of 80-100 μm are selected and used; alloy powders are prepared, wherein, by mass fraction, Ni60A self-fluxing alloy powder accounts for 90%, nickel-coated graphite accounts for 5%, and titanium carbide accounts for 5%; a binder is added, wherein the binder is powdered paraffin wax, and the addition amount is 3% of the alloy powder; the alloy powder mixed with the paraffin wax powder is mixed by a powder mixer, the mixing speed is 1000 rpm, and the mixing time is 2 minutes; 6 g of powder is weighed and added into a disc mold with a diameter of 20 mm for pressing, and the pressure is 24 tons.

[0077] Put the pressed sample into the vacuum sintering furnace, and after the vacuum degree in the furnace chamber is pumped to -1 bar, dewaxing sintering is carried out to decompose the paraffin in the powder into gas and remove it. Dewaxing sintering is divided into two stages. The sintering temperature of the first stage is 300℃, the sintering time is 1 hour, and the sintering temperature of the second stage is 400℃, the sintering time is 1 hour. The heating rate from room temperature to the first and second sintering stages is controlled at 3℃ / min. After dewaxing sintering is completed, metallurgical sintering is carried out. There is no need to open the furnace, continue to heat up to 1050℃, the heating rate is 10℃ / min, keep warm at 1050℃ for 2 hours, cool to 150℃ with the furnace and take it out.

[0078] like Figure 3 As shown in the figure (a is the surface morphology of the wear scar, and b is the cross-sectional profile of the wear scar), it is a schematic diagram of the wear scar depth and wear scar profile of the sample (T5G5) in Example 2, with a TiC addition of 5% and a nickel-coated graphite addition of 5%, a sintering parameter of 1050°C, and a reciprocating friction condition of 40N, 5mm reciprocating stroke, and 300t / min reciprocating speed.

[0079] Figure 3 The surface morphology and cross-sectional profile of the wear scar of T5G5 are given. Figure 3 (a) shows that the wear marks of the T5G5 sample are relatively uniform, and the fine scratches on the surface indicate that the surface was cut by the particles during the friction process. At the same time, there are a certain number of pits on the sample surface. During the friction process, graphite peels off and exists in the pits, but due to the discrete distribution of the pits, the lubrication effect of the graphite is not obvious. Figure 3(b) shows that the wear scar depth of the T5G5 sample varies relatively little, and the depth curves between the lines are relatively close, indicating that the depth distribution of the wear scar is uniform and the depth of the wear scar is about 20 μm.

[0080] Embodiment 3:

[0081] Ni60A powder with a particle size of 60-80 μm, TiC powder with a particle size of 1-15 μm and nickel-coated graphite powder with a particle size of 80-100 μm are selected; alloy powders are prepared, wherein, by mass fraction, Ni60A self-fluxing alloy powder accounts for 85%, nickel-coated graphite accounts for 10%, and titanium carbide accounts for 5%; a binder is added, wherein the binder is powdered paraffin wax, and the addition amount is 3% of the alloy powder; the alloy powder mixed with the paraffin wax powder is mixed by a powder mixer, the mixing speed is 1000 rpm, and the mixing time is 2 minutes; 6 g of powder is weighed and added into a disc mold with a diameter of 20 mm for pressing, and the pressure is 24 tons.

[0082] Put the pressed sample into the vacuum sintering furnace, and after the vacuum degree in the furnace chamber is pumped to -1 bar, dewaxing sintering is carried out to decompose the paraffin in the powder into gas and remove it. Dewaxing sintering is divided into two stages. The sintering temperature of the first stage is 300℃, the sintering time is 1 hour, and the sintering temperature of the second stage is 400℃, the sintering time is 1 hour. The heating rate from room temperature to the first and second sintering stages is controlled at 3℃ / min. After dewaxing sintering is completed, metallurgical sintering is carried out. There is no need to open the furnace, continue to heat up to 1050℃, the heating rate is 10℃ / min, keep warm at 1050℃ for 2 hours, cool to 150℃ with the furnace and take it out.

[0083] like Figure 4 As shown in the figure (a is the surface morphology of the wear scar, and b is the cross-sectional profile of the wear scar), it is a schematic diagram of the wear scar depth and wear scar profile of the sample (T5G10) in Example 3, with a TiC addition of 5% and a nickel-coated graphite addition of 10%, a sintering parameter of 1050°C, and a reciprocating friction condition of 40N load, 5mm reciprocating stroke, and 300t / min reciprocating speed.

[0084] Figure 4 The surface morphology and cross-sectional profile of the T5G10 wear scar are given. Figure 4 (a) shows that the wear scar morphology of the T5G10 sample is relatively uniform, and the surface shows fewer deep pits and scratches compared to T5G5, indicating that the lubrication of graphite plays a significant role in the friction process, reducing local wear and reducing the volatility of overall wear. The presence of graphite as a lubricating phase helps to form a lubricating film at the friction interface, thereby reducing the adhesion and shedding of surface materials.

[0085] The wear scar depth of the T5G10 sample is relatively shallow, about 20μm, and the fluctuation amplitude of the cross-sectional profile is small, showing a relatively consistent wear depth. This is in contrast to the T5G5 sample, which has a similar wear scar depth but a less smooth wear scar profile. This further proves the lubrication effect of graphite, which effectively reduces the friction coefficient and reduces excessive wear in local areas of the material surface.

[0086] Embodiment 4:

[0087] Ni60A powder with a particle size of 60-80 μm, TiC powder with a particle size of 1-15 μm and nickel-coated graphite powder with a particle size of 80-100 μm are selected; alloy powders are prepared, wherein, by mass fraction, Ni60A self-fluxing alloy powder accounts for 80%, nickel-coated graphite accounts for 10%, and titanium carbide accounts for 10%; a binder is added, wherein the binder is powdered paraffin wax, and the addition amount is 3% of the alloy powder; the alloy powder mixed with the paraffin wax powder is mixed by a powder mixer, the mixing speed is 1000 rpm, and the mixing time is 2 minutes; 6 g of powder is weighed and added into a disc mold with a diameter of 20 mm for pressing, and the pressure is 24 tons.

[0088] Put the pressed sample into the vacuum sintering furnace, and after the vacuum degree in the furnace chamber is pumped to -1 bar, dewaxing sintering is carried out to decompose the paraffin in the powder into gas and remove it. Dewaxing sintering is divided into two stages. The sintering temperature of the first stage is 300℃, the sintering time is 1 hour, and the sintering temperature of the second stage is 400℃, the sintering time is 1 hour. The heating rate from room temperature to the first and second sintering stages is controlled at 3℃ / min. After dewaxing sintering is completed, metallurgical sintering is carried out. There is no need to open the furnace, continue to heat up to 1050℃, the heating rate is 10℃ / min, keep warm at 1050℃ for 2 hours, cool to 150℃ with the furnace and take it out.

[0089] like Figure 5 As shown in the figure (a is the surface morphology of the wear scar, and b is the cross-sectional profile of the wear scar), it is a schematic diagram of the wear scar depth and wear scar profile of the sample (T10G10) in Example 4, with a TiC addition of 10% and a nickel-coated graphite addition of 10%, a sintering parameter of 1050°C, and a reciprocating friction condition of 40N, 5mm reciprocating stroke, and 300t / min reciprocating speed.

[0090] Figure 5 The surface morphology and cross-sectional profile of the wear scar of T10G5 are given. Figure 5(a) shows that there are large pits on the wear surface similar to T5G10. Thanks to the friction reduction effect of graphite in the pits, the wear scar of T10G10 sample is shallow. The presence of large pits indicates that when the nickel-coated graphite content reaches 10%, the overall strength of the matrix is ​​damaged, which weakens the surface strengthening effect brought by the high TiC content, making the wear loss of Ti10G10 higher than that of Ti10G5.

[0091] Comparative Example 1:

[0092] Ni60A powder with a particle size of 60-80 μm is selected and a binder is added. The binder is powdered paraffin, and the addition amount is 3% of the alloy powder; the alloy powder mixed with paraffin powder is mixed using a powder mixer, the mixing speed is 1000 rpm, and the mixing time is 2 minutes; 6 g of powder is weighed and added to a disc mold with a diameter of 20 mm for pressing at a pressure of 24 tons.

[0093] Put the pressed sample into the vacuum sintering furnace, and after the vacuum degree in the furnace chamber is pumped to -1 bar, dewaxing sintering is carried out to decompose the paraffin in the powder into gas and remove it. Dewaxing sintering is divided into two stages. The sintering temperature of the first stage is 300℃, the sintering time is 1 hour, and the sintering temperature of the second stage is 400℃, the sintering time is 1 hour. The heating rate from room temperature to the first and second sintering stages is controlled at 3℃ / min. After dewaxing sintering is completed, metallurgical sintering is carried out. There is no need to open the furnace, continue to heat up to 1050℃, the heating rate is 10℃ / min, keep warm at 1050℃ for 2 hours, cool to 150℃ with the furnace and take it out.

[0094] like Figure 6 As shown in the figure (a is the surface morphology of the wear scar, and b is the cross-sectional profile of the wear scar), it is a schematic diagram of the wear scar depth and wear scar profile of the sample (T0G0) in comparative example 1, with a TiC addition of 0% and a nickel-coated graphite addition of 0%, a sintering parameter of 1050°C, and a reciprocating friction condition of 40N, 5mm reciprocating stroke, and 300t / min reciprocating speed.

[0095] Figure 6 The surface morphology and cross-sectional profile of the wear scar of T10G5 are given. Figure 5 (a) shows that there are large pits on the wear scar surface. Due to the absence of TiC hard phase reinforcement and friction reduction effect of graphite, the wear scar of T0G0 sample is relatively deep.

[0096] Figure 7Schematic diagram of the change of friction coefficient over time of the samples obtained in Examples 1, 2, 3, 4 and Comparative Example 1 in the friction and wear test (i.e., the change of friction coefficient over time of the five samples with different compositions T5G5, T5G10, T10G5, T10G10 and T0G0 in the friction and wear test);

[0097] according to Figure 7 The change of friction coefficient over time of four samples in friction and wear experiments is given. As can be seen from the figure, the friction coefficient of T5G5 sample gradually increases over time and reaches about 0.4 at nearly 30 minutes. This trend shows that friction gradually intensifies during the wear process. This is because the wear resistance of the sample surface is poor, resulting in severe surface wear, and the friction force gradually increases with the increase of contact area.

[0098] T5G10 showed a high friction coefficient at the beginning of the experiment, and the friction coefficient reached a peak at 5 minutes, then gradually decreased and stabilized, and finally stabilized at about 0.3. This shows that during the initial running-in process, the sample surface experienced greater friction, and over time, a relatively stable lubrication layer was formed on the surface, keeping the friction coefficient relatively stable.

[0099] The friction coefficient of the T10G sample rose slowly at the beginning of the experiment, reached a peak value at about 10 minutes, then gradually decreased and stabilized, and finally maintained at about 0.26. The peak value of the friction coefficient of T10G5 was delayed compared with T5G10, which shows that the increase in TiC content gives the sample better wear resistance, allowing the graphite in it to form a relatively stable and smooth friction layer in the future.

[0100] The friction coefficient of T10G10 fluctuates stably around 0.25, indicating that the increase in the content of nickel-coated graphite has no obvious friction reduction effect for samples with a TiC content of 10%.

[0101] Figure 8 (In the figure, a is the density change diagram, and b is the porosity change diagram) is a schematic diagram of the density and porosity changes of five samples with different compositions, T5G5, T5G10, T10G5, T10G10 and T0G0, under different sintering parameters.

[0102] Fig. 9The figure shows the depth and cross-sectional area of ​​the wear scars of T5G5, T5G10, T10G5, T10G10 and T0G0 in the friction and wear test. It can be found that the increase of TiC significantly reduces the depth and cross-sectional area of ​​the wear scars. TiC, as a hard reinforcing phase, increases the overall hardness and wear resistance of the material and reduces the amount of wear of the material during the friction process. In particular, the T10G5 sample, due to the 10% TiC content, shows the smallest wear scar depth and cross-sectional area, which indicates that TiC effectively improves the wear resistance of the material.

[0103] At lower TiC content, the increase in graphite content helps to reduce the friction coefficient and the depth and cross-sectional area of ​​the wear scar. However, at higher TiC content, due to the high graphite content of the T10G10 sample, on the one hand, the reinforcing effect of TiC on the matrix is ​​weakened, and on the other hand, the stress distribution during friction and wear is uneven, which ultimately increases the size of the wear scar.

[0104] In summary, nickel-coated graphite is added as a lubricating phase in the TiC enhancement scheme. In this embodiment, four powder compositions of T5G5, T5G10, T10G5 and T10G10 are tested, and the powder composition without adding TiC and graphite in the conventional scheme is compared. The experiment first determined that 1050°C and 2h are the best sintering parameters. On this basis, it is found that TiC is the main wear resistance enhancement phase. The higher the TiC, the better the wear resistance; nickel-coated graphite is a good lubricating phase. The higher the content, the lower the friction coefficient; nickel-coated graphite is also a good bonding phase. The higher the content, the lower the porosity of the sample after sintering; graphite promotes the galvanic corrosion process during the corrosion process, which is harmful to the corrosion resistance. According to the results of electrochemical tests and friction and wear tests, the T10G5 scheme has the best corrosion resistance and wear resistance.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-lubricating nickel-based composite material, characterized in that: The following raw materials are included in mass percentage: Nickel-coated graphite powder 4.9%-6.8%, TiC powder 9.7%-11.7%, Ni60A powder 81.6%-82.5% and binder 2.4%-2.9%.

2. A self-lubricating nickel-based composite material according to claim 1, characterized in that: The particle size of the nickel-coated graphite powder is 80 μm-100 μm, the particle size of the TiC powder is 1 μm-15 μm, and the particle size of the Ni60A powder is 60 μm-80 μm.

3. The self-lubricating nickel-based composite material according to claim 1, characterized in that: The binder is powdered paraffin.

4. A powder metallurgy forming method for a self-lubricating nickel-based composite material, characterized in that: The method includes: The mass percentage of each raw material is set based on the metallurgical forming requirements, and the corresponding mass percentages of nickel-coated graphite powder, TiC powder, Ni60A powder and binder are weighed; The alloy powder mixed with the binder is mixed by using a mixing device, and the mixed powder is weighed and added into a disc mold for pressing to obtain a sample; The pressed sample is placed in a vacuum sintering furnace, dewaxing and sintering treatment is performed in the vacuum sintering furnace, and metallurgical sintering treatment is performed after the dewaxing and sintering is completed to obtain a circular wear-resistant and corrosion-resistant gasket.

5. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: The mass percentages of the raw materials include: 4.9%-6.8% of nickel-coated graphite powder, 9.7%-11.7% of TiC powder, 81.6%-82.5% of Ni60A powder and 2.4%-2.9% of binder.

6. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: The mass percentages of the raw materials include: 4.9% nickel-coated graphite powder, 9.7% TiC powder, 82.5% Ni60A powder and 2.9% binder.

7. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: The particle size of the nickel-coated graphite powder is 80 μm-100 μm, the particle size of the TiC powder is 1 μm-15 μm, and the particle size of the Ni60A powder is 60 μm-80 μm.

8. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: The binder is powdered paraffin.

9. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: The mixing device is a powder mixer, and the rotation speed of the mixing process is 1000 rpm, and the mixing time is 2 minutes.

10. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: The mass of the mixed powder is 6 g, the diameter of the disc mold is 200 mm, and the pressure during the pressing process is 24 t.

11. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: During the dewaxing sintering process, the vacuum degree in the chamber of the vacuum sintering furnace is -1 bar.

12. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: The dewaxing sintering process includes two stages, wherein the sintering temperature of the first stage is 300℃-320℃, and the sintering time is 30min-60min, and the sintering temperature of the second stage is 380℃-400℃, and the sintering time is 30min-60min. The heating rate from room temperature to the first and second sintering stages is 3℃ / min.

13. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: The dewaxing and sintering process includes two stages, wherein the sintering temperature of the first stage is 300° C. and the sintering time is 1 hour, and the sintering temperature of the second stage is 400° C. and the sintering time is 1 hour.

14. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: There is no need to open the furnace during metallurgical sintering treatment. Continue to heat up to 1040℃-1050℃ at a heating rate of 10℃ / min. After sintering for 100min-120min, cool down to 150℃ with the furnace and take out.

15. The powder metallurgy forming method of a self-lubricating nickel-based composite material according to claim 4, characterized in that: During the metallurgical sintering treatment, there is no need to open the furnace, and the temperature is continued to rise to 1050°C at a rate of 10°C / min. After being kept at 1050°C for 2 hours, it is cooled to 150°C with the furnace and taken out.

16. Use of the self-lubricating nickel-based composite material according to claim 1 or the self-lubricating nickel-based composite material prepared by the powder metallurgy forming method of the self-lubricating nickel-based composite material according to claim 4 in wear-resistant parts.